XSLT, 2nd Edition - Tidwell, Doug (O'Reilly Media, 2011)
After years of anticipation and delay, the W3C finally released the XSLT 2.0 standard in January 2007. The revised edition of this classic book offers practical, real-world examples that demonstrate how you can apply XSLT stylesheets to XML data using either the new specification, or the older XSLT 1.0 standard.